Synergistic effects of aquatic weed biochar and inorganic fertilizer on soil properties, maize yield, and nitrogen use efficiency on Nitisols of Northwestern Ethiopian Highlands - Gezahegn, Ashenafei; Selassie, Yihenew G.; Agegnehu, Getachew; Addisu, Solomon; Mihretie, Fekremariam A.; Kohira, Yudai; Lewoyehu, Mekuanint; Sato, Shinjiro (Elsevier, 2025)
Soil acidity and poor fertility limit crop production in Ethiopia. Biochar from organic wastes, such as water hyacinth (Eichhornia crassipes), offers a potential solution. This study investigated the effects of co-applying water hyacinth biochar (WHB) with inorganic fertilizers on soil characteristics, maize yield, and nitrogen (N) use efficiency under field conditions. Four rates of WHB (0, 5, 10, and 20 t ha−1) were combined with two levels of recommended inorganic fertilizers (half and full rates of 180/138 kg N/P2O5 ha−1), plus a control (no biochar/fertilizer), during the 2022 and 2023 growing seasons. Results indicated that WHB significantly improved soil physicochemical properties (p < 0.05), across fertilizer rates, demonstrating both additive and independent effects. Consequently, WHB application reduced bulk density, increased porosity, and soil pH, and decreased exchangeable acidity and exchangeable Al3+, with the 20 t ha−1 WHB rate eliminating exchangeable Al3+. Moreover, available phosphorus, organic carbon, total nitrogen, cation exchange capacity, and exchangeable potassium were significantly improved (p < 0.05). Co-applying WHB with half and full rates of chemical fertilizers enhanced maize grain yield by 33.6 % and 30.8 %, respectively, compared to sole half and full fertilizer rates (non-biochar), with yield increases of up to 10 % in the second year compared to the first. Maize total biomass and 1000-grain weight also showed significant improvements. Nitrogen use efficiency significantly improved, especially when WHB was used with half the fertilizer level. These findings demonstrate the potential of combining WHB with inorganic fertilizers to improve soil fertility and enhance crop production in acidic soils.